Slovenian development cooperation and commercial diplomacy - Arbeiter, Jana (Teorija in praksa, 2019)
Slovenia's commercial diplomacy is older than 25 years, as is its international development cooperation, despite the fact Slovenia graduated from being a recipient to a donor in December 2004. One may have expected that, by now, the relationship between the two foreign policy instruments would be fully integrated into the institutional framework. Yet, as the article shows, this is not the case. Several factors impact and blur the relationship between them: the lack of a structural approach, insufficient institutional support, and fragmentation of both activities. With all three factors in mind, we analysed whether both can operate as complementary activities, even though they are currently regarded as supplementary ones. The expected policy coherence has not been automatically established between the two activities, as one might have assumed.
Keywords: Development aid; Diplomacija; Diplomacy; Foreign policy; gospodarska diplomacija; International cooperation; Mednarodno sodelovanje; Razvojna pomoč; Zunanja politika